Effects of malondialdehyde content in low density lipoproteins on platelet adhesion - Suttnar, J; Otáhalová, E; Cermák, J; Dyr, J E (Platelets, 2006)
Platelets play a key role in thrombotic vascular occlusion at the side of an atherosclerotic plaque. Malondialdehyde (MDA) derivatives are components of oxidized LDL. Recent studies suggest enhanced adhesion of platelets on oxidized LDL, but evidence of MDA-modified LDL contribution to enhanced platelet adhesion is missing. The aim of this study was to investigate platelet adhesion on LDLs with various content of MDA and to analyze its physiological relevance. LDLs were isolated by hydroxyapatite chromatography then analyzed. MDA, vitamin E and vitamin A content was estimated by HPLC methods and adhesion of platelets on modified LDLs was assessed. Both MDA and hypochlorite reactions induced an increase of both malondialdehyde content and negative charge in LDLs preparations. In LDLs of iron-overloaded patients both MDA content and negative charge was also significantly increased. The analysis of data showed that enhanced negative charge of LDLs had only negligible influence on platelet adhesion. The binding of platelets on LDL particles modified by MDA resulted in an S-shape curve and was substantially enhanced by high levels of MDA in LDL preparations. Malondialdehyde content both in hypochlorite modified LDLs and in LDLs of iron-overloaded patient matched the lower part of the binding curve. The platelet adhesion on circulating LDLs modified in in vivo conditions of oxidation stress in blood of iron-overloaded patients depends with considerable certainty preferably on non-MDA derived changes in derivatized LDLs. On the other hand, oxidized LDLs in atherosclerotic lesions can be much more extensively modified by MDA resulting in surfaces with enhanced affinity to adhering platelets. Such LDLs may be accessible to platelets, due to endothelial denudation or plaque rupture.
Keywords: Hypochlorous Acid; Platelet Adhesiveness; časové faktory; malondialdehyd; Time Factors; lidé; Lipoproteins, LDL; kyselina chlorná; chromatografie; Chromatography; Malondialdehyde; lipoproteiny LDL; adhezivita trombocytů; Humans